Role of glutathione transferases in the improved acclimation to salt stress in salicylic acid-hardened tomato - Csiszár, Jolán (Acta Biologica Szegediensis, 2011)
Three weeks old Solanum lycopersicum L. cvar. Rio Fuego plants , which grew in hydroponic culture, were pre-treated with 10-7 M or 10-4 M salicylic acid (SA) and 100 mM NaCl was added to the nutrient solution from the 6th week. The activity of glutathione transferase (GST), glutathione peroxidase (GPOX) and dehydroascorbate reductase (DHAR) were analyzed spectrophotometrically after one week salt stress. All of these activities are connected to GST enzyme family, but the changes were different at the end of the pre-treatment or after the NaCl stress. SA enhanced the GPOX activity in the highest extent by the end of the three-week-period, while in glutathione transferase function there was no significant changes. The salt treatment mostly enhanced these enzyme activities but in the SA-pre-treated plants the GST and GPOX activities were elevated in a higher extent. In contrast to the lower SA concentration, pre-treatment with 10-4 M SA maintained the DHAR activities at the control level even in roots. Our results indicate that the increased antioxidant enzyme activities may be the part of the hardening effect of SA. GSTs can participate in the maintenance of the redox state of cells and improving the salt stress tolerance of tomato plants.